IMPLEMENTASI WAHTAPP CHATBOT BERBASIS KECERDASAN BUATAN (AI) UNTUK MENINGKATKAN EFISIENSI LAYANAN SERTIFIKASI DI LSP POLITEKNIK NEGERI SRIWIJAYA PALEMBANG - Agus Setiawan; Yudistira Sira Permana; Meilyana Winda Perdana (LPPM UNIVERSITAS BINA INSAN, 2026)
The Sriwijaya State Polytechnic Professional Certification Institute (LSP) faces the challenge of manual certification information services, causing response delays and high administrative burdens. This study aims to implement an artificial intelligence (AI)-based chatbot to improve the efficiency of certification services, in line with the Smart ASN concept and BerAKHLAK values. The development method includes FAQ research, flow design, technical construction with WhatsApp Business API integration, validation through User Acceptance Test (UAT), and full implementation. The chatbot utilizes Natural Language Processing (NLP) to provide information on certification schemes, requirements, and schedules automatically 24 hours a day.. The results show that the chatbot is able to handle routine questions independently, reduce staff workload, and significantly speed up response times. This implementation supports the digital transformation of innovative and responsive public service.